Steeping from green and black robusta coffee beans increase viability of Peripheral Blood Mononuclear Cells (PBMC) and salivary leukocytes which is induced by streptococcus mutans - I-Dewa A.R. Dewanti; Roedy Budirahardjo; Ristya WE. Yani; Pujiana E. Lestari; Dyah Setyorini; Eri H. Jubhari; Sunlip Wibisono (DiscoverSys Inc., 2019)
Objective: Analyzing viability of PBMC and salivary leukocytes Â by steeping green coffee and black coffee seeds from Robusta coffee after induced with S. mutans.Material and Methods: Blood and saliva of healthy people added with histopaque centrifugation and suspended in RPMI 1640. The cells were placed in 24-well microtiter plate, treated according to group. The research groups: control: induced by S. mutans, black coffee (2.5%, 5%, 10%), Green coffee (2.5%, 5%, 10%). All coffee groups, both PBMC and saliva groups were induced by S. mutans. Viability was stainted with Tripan Blue. Cells were counted under an inverted microscope with magnification 400 times from an average of 5 fields of view. The data obtained were ANOVA followed by LSD test.Results. ANOVA and LSD analysis showed significant differences (0.01<p). The higher of concentration of Robusta coffee, the more cells that live. On the other hand, Green coffee increased the viability of PBMC and salivary leucocytes more than black coffee. Suspected, because antioxidant of the green coffee that more higher than black coffee, so it is better able to protect cells.Conclusion. Steeping Green and black coffee increase viability of PBMC and leucocytes which is induced by S. mutans.